2019
DOI: 10.1002/jbt.22345
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic investigations of the liver toxicity of the free fatty acid receptor 1 agonist fasiglifam (TAK875) and its primary metabolites

Abstract: For fasiglifam (TAK875) and its metabolites the substance‐specific mechanisms of liver toxicity were studied. Metabolism studies were run to identify a putatively reactive acyl glucuronide metabolite. In vitro cytotoxicity and caspase 3/7 activation were assessed in primary human and dog hepatocytes in 2D and 3D cell culture. Involvement of glutathione (GSH) detoxication system in mediating cytotoxicity was determined by assessing potentiation of cytotoxicity in a GSH depleted in vitro system. In addition, pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…In the viability study, TAK-875 showed an IC 50 of approximately 50 μM, which was in line with the values reported in initial studies detailing TAK-875 toxicity ( Fig 1 ) [ 25 ]. This was also in agreement with a more recent study by others who reported IC 50 values of 68 and 56 μM when the time of incubation was 24 and 48 h, respectively [ 45 ]. Authors underscored that the longer hepatocytes were incubated with the compound, the more sensitive they become to toxicity of the compound.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the viability study, TAK-875 showed an IC 50 of approximately 50 μM, which was in line with the values reported in initial studies detailing TAK-875 toxicity ( Fig 1 ) [ 25 ]. This was also in agreement with a more recent study by others who reported IC 50 values of 68 and 56 μM when the time of incubation was 24 and 48 h, respectively [ 45 ]. Authors underscored that the longer hepatocytes were incubated with the compound, the more sensitive they become to toxicity of the compound.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, TAK-875 impaired mitochondrial function and caused DNA damage. TAK-875 also reduced glutathione content in the cells, and even though it was reported elsewhere of no account for TAK-875 toxicity, it might still underlie the observed elevated oxidative stress ( Table 1 ) [ 45 ]. Regarding the deleterious effects of the parent molecule, it has been proposed that glucuronide (TAK-875-Glu), one of the main metabolites of TAK-875, might accumulate aside TAK-875 in the liver, thus causing additional injuries.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ezetimibe-G, a substrate of OATPs and MRP2, is also a strong inhibitor of OATPs (half maximal inhibitory concentration (IC 50 ) <0.5 µM) and can inhibit BCRP, MRP2 and MRP3 ( Oswald et al, 2008 ; de Waart et al, 2009 ). Another drug conjugate with strong inhibition potential for both OATP1Bs and MRPs is fasiglifam-G, which has IC 50 values ≤1 µM for these transporters ( Otieno et al, 2018 ; Ackerson et al, 2019 ). Raloxifene-4′-G and raloxifene-6,4′-di-G appear able to inhibit all of the major hepatic drug transporters with IC 50 values <10 µM, but interpretation warrants caution as values for the efflux transporters are based on changes in ATPase activity and not inhibition of transport ( Trdan Lušin et al, 2012a ; 2012b ).…”
Section: Conjugates As Inhibitors Of Transportersmentioning
confidence: 99%
“…In addition, TAK-875 and zamifenacin were reported to be metabolized by CYPs. 25,26 The toxicity of ADX-10059 in HepG2 cells increased under galactose culture condition (Fig. 5), and that of TC-Hep cells was the same as that of HepG2 cells (Fig.…”
Section: Evaluation Of Discontinued Compounds Due To Liver Injurymentioning
confidence: 88%